2n-3=13+6n

Simple and best practice solution for 2n-3=13+6n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2n-3=13+6n equation:



2n-3=13+6n
We move all terms to the left:
2n-3-(13+6n)=0
We add all the numbers together, and all the variables
2n-(6n+13)-3=0
We get rid of parentheses
2n-6n-13-3=0
We add all the numbers together, and all the variables
-4n-16=0
We move all terms containing n to the left, all other terms to the right
-4n=16
n=16/-4
n=-4

See similar equations:

| -4-5x=-8-6x | | 3(x-1)-8=4(1+x)=+5 | | 4(x-3)+6=4x-5 | | 39=13z | | 9)-5x-9=-153+7x | | -4(4n+3.5=) | | 5x+8x=11+2x | | -6g-4=3g-20-7g | | 8(j-82)=80 | | 31/4+4=5p | | 2(x-6)+5=2x-7 | | 16=4(u-80) | | -42-8x=-24-2x | | 2+4p=p+17 | | 3b+7=2b+17 | | 8(w+52)=96 | | (20p-8)=32 | | 4x-10=6x-24 | | 9(x3)=2x+83 | | 4p+7=-8 | | (4y+8)=-24 | | 180-125+4x=180 | | 90=6(b+7) | | 2=v/4-3 | | (10x^2)=(19-10x) | | 180-125+4x=0 | | 31-p=419 | | 10(j+7)=90 | | -3(x=5)=8x+18 | | -6x+8=−6x+8=-10x-20 | | 13=90x-4 | | 7(n-94)=7 |

Equations solver categories